The Impact of Library Resource Utilization on Undergraduate Students’ Academic Performance: A Propensity Score Matching Design - Chiteng Kot, Felly; Jones, Jennifer L. (College and Research Libraries, 2015)
This study uses three cohorts of first-time, full-time undergraduate students (N=8,652) at a large, metropolitan, public research university to examine the impact of student use of three library resources (workstations, study rooms, and research clinics) on academic performance. To deal with self-selection bias and estimate this impact more accurately, we used propensity score matching. Using this unique approach allowed us to construct treatment and control groups with similar background characteristics. We found that using a given library resource was associated with a small, but also meaningful, gain in first-term grade point average, net of other factors.
Keywords: undergraduate students; рабочее место; учебный зал; исследовательские клиники